It is for pleasure, not for my English: Insights into Indonesian adolescent online story readers - Winda Setia Sari; Faruk S. U.; Ursula Hurley (Indonesian Journal of Applied Linguistics, 2023)
Reading motivation has been extensively studied in online reading settings. However, not much is known about what makes people want to read fiction online, especially in a foreign-language setting. As part of the growth of digital literature and cybernetics, online fiction is gaining popularity among young Indonesians. This research sought to explore Indonesian EFL adolescent readers’ motivations and preferences as they engage in reading online stories in English. 112 university students responded to a survey, and 14 of them were chosen at random for in-depth interviews to learn more about their reading preferences and cybernetic literary practices. Analysis of the survey data showed that most readers chose Wattpad and Webtoon as their favorite online platforms, and romance and fantasy as their favorite genres. They devoted many hours to reading novels on these platforms to seek enjoyment and improve their English vocabulary and language. Yet, data from the interviews further revealed that adolescent readers claimed to read solely to seek enjoyment and pleasure. Also, readers were mostly silent, unwilling to participate in online conversations between readers and reader-authors but actively rating the novels after reading. Findings contribute to establishing views on reading motivation and cybernetic literary practices for EFL fiction readers; reading for pleasure is the intrinsic motivation that triggers Indonesian adolescent readers to stay online on the platform.